Educational Financing and Professional Allowances as Determinants of Teacher Welfare in Islamic Educational Institutions: A Literature Study on the Role of Edupreneurship as a Teacher Empowerment Strategy - Holilur Rahman; Sulistia Ningrum; Uswatun Hasanah; Ati’atur Robbaniyah; Annawiyah, Annawiyah; Halimi, Halimi (Responsive: Jurnal Manajemen Pendidikan Islam, 2025)
Teacher welfare is a key factor in improving the quality of education, but to date it remains a fundamental issue both globally and nationally. Although the Indonesian government has allocated significant funding for education, including professional allowances as a means of improving teacher professionalism and welfare, the reality on the ground shows that the welfare gap is still very pronounced. Civil servant teachers tend to earn a stable income, while millions of contract teachers still face economic constraints that affect their motivation and performance. At the same time, technological developments and the digitization of education have opened up opportunities for teachers to develop edupreneurship as a strategy for increasing income and developing competencies. However, teachers' ability to participate in educational entrepreneurship activities is greatly influenced by their level of welfare, including the effectiveness of education funding and the distribution of professional allowances. This study aims to analyze the role of education funding and professional allowances as determinants of teacher welfare, as well as how this welfare affects teacher participation in edupreneurship as a form of economic empowerment. Using a qualitative approach based on literature review, this study found that improved teacher welfare has a strong correlation with their ability to innovate, develop digital skills, and engage in edupreneurship activities. These findings emphasize the need for more equitable, sustainable, and responsive education financing policies that address teachers' needs in order to support professional empowerment while improving the quality of national education.